Effectiveness of a stepped-care programme of internet-based psychological interventions for healthcare workers with psychological distress: Study protocol for the RESPOND healthcare workers randomised controlled trial. (October 2022) - Mediavilla, Roberto; McGreevy, Kerry R; Felez-Nobrega, Mireia; Monistrol-Mula, Anna; Bravo-Ortiz, María-Fe; Bayón, Carmen; Rodríguez-Vega, Beatriz; Nicaise, Pablo; Delaire, Audrey; Sijbrandij, Marit; Witteveen, Anke B.; Purgato, Marianna; et al.
Background and aims: The coronavirus disease 2019 pandemic has challenged health services worldwide, with a worsening of healthcare workers' mental health within initial pandemic hotspots. In early 2022, the Omicron variant is spreading rapidly around the world. This study explores the effectiveness and cost-effectiveness of a stepped-care programme of scalable, internet-based psychological interventions for distressed health workers on self-reported anxiety and depression symptoms. Methods: We present the study protocol for a multicentre (two sites), parallel-group (1:1 allocation ratio), analyst-blinded, superiority, randomised controlled trial. Healthcare workers with psychological distress will be allocated either to care as usual only or to care as usual plus a stepped-care programme that includes two scalable psychological interventions developed by the World Health Organization: A guided self-help stress management guide (Doing What Matters in Times of Stress) and a five-session cognitive behavioural intervention (Problem Management Plus). All participants will receive a single-session emotional support intervention, namely psychological first aid. We will include 212 participants. An intention-to-treat analysis using linear mixed models will be conducted to explore the programme's effect on anxiety and depression symptoms, as measured by the Patient Health Questionnaire – Anxiety and Depression Scale summary score at 21 weeks from baseline. Secondary outcomes include post-traumatic stress disorder symptoms, resilience, quality of life, cost impact and cost-effectiveness. Conclusions: This study is the first randomised trial that combines two World Health Organization psychological interventions tailored for health workers into one stepped-care programme. Results will inform occupational and mental health prevention, treatment, and recovery strategies. Registration details: ClinicalTrials.gov Identifier: NCT04980326.